Philo of Alexandria: A model for early Christian "spiritual readings" of the Scriptures - Decock, Paul Bernard (HTS teologiese studies, 2015)
Philo of Alexandria represents a Hellenistic tradition of reading the Scriptures in which reading is seen as a spiritual exercise together with other spiritual exercises, like attention, thorough investigation of the issues, self-mastery, detachment, etcetera (see Her. 253; Leg. 3:18), which has as aim the transformation and growth of the person towards the good and happy life. Interaction with the spiritual wealth of the Greek philosophical traditions was seen as a fruitful asset and challenge. This article highlights some of the key themes of Philo’s philosophical or spiritual reading of the Scriptures: the priority of God and of the health of the soul, the importance of human progress, the recognition of one’s nothingness in order to know God, the necessity to choose, human effort and divine achievement, as well as harmony with God, nature and the self as the aims of the good life. Christian spiritual writers, like Origen, found in Philo’s approach to the Scriptures and in his reflections on the spiritual journey a very inspiring model.